Desmoplastic mesenteric lesions do not respond radiographically to peptide receptor radionuclide therapy - Pelle, Eleonora; Al‐Toubah, Taymeyah; Morse, Brian; El‐Haddad, Ghassan; Strosberg, Jonathan (Journal of neuroendocrinology, 2021)
177Lu‐Dotatate treatment is indicated for progressive, well‐differentiated, small bowel neuroendocrine tumours) NETs. These tumours often metastasise to mesenteric lymph nodes and produce a desmoplastic reaction, consisting of tumour cells interspersed with fibrotic tissue. We hypothesised that, in patients treated with 177Lu‐Dotatate, mesenteric tumours would remain stable even as liver tumour size changes were observed. We retrospectively reviewed the records of all patients treated with 177Lu‐Dotatate between April 2018 and December 2019. Among patients with desmoplastic mesenteric tumours and liver metastases, we evaluated changes in tumour size of mesenteric and liver lesions based on pre‐ and post‐treatment anatomic scans. As a result of the infrequency of objective radiographic response, any reported changes in tumour size were considered significant. Twenty‐one patients met the inclusion criteria: nine had evidence of shrinkage of liver lesion(s), one had mild progression of liver lesions, seven had stable hepatic disease and four had a mixed hepatic response. Two of the patients with hepatic tumour shrinkage met the criteria for a partial response via RECIST 1.1 (https://recist.eortc.org). Desmoplastic mesenteric lesions remained unchanged in size, regardless of the changes detected in liver lesions. In conclusion, 177Lu‐Dotatate does not impact desmoplastic mesenteric tumours which are typically associated with midgut NETs. Patients whose disease is predominantly confined to desmoplastic mesenteric lesions are unlikely to respond radiographically to peptide receptor radionuclide therapy. Moreover, the inclusion of desmoplastic mesenteric lesions as target lesions in RECIST measurements tends to increase rates of disease stability vs response or progression. Desmoplastic mesenteric metastases are common in patients with advanced small‐intestinal neuroendocrine tumours. Our analysis indicates that these particular tumours do not respond to peptide receptor radionuclide therapy, even when liver metastases respond.